Dynamic strain anomalies detection at Stromboli before 2019 vulcanian explosions using machine learning - Romano, Pierdomenico; Di Lieto, Bellina; Scarpetta, Silvia; Apicella, Ilenia; Linde, Alan T.; Scarpa, Roberto (Frontiers in Earth Science, 2022)
During the summer of 2019, Stromboli experienced two paroxysmal eruptions that occurred in two different volcanic phases: the eruption on July, 3 was clearly preceded by smaller and less perceptible changes in the volcano dynamics, while the second eruption, on August 28 at the very end of the explosive sequence, concluded the eruptive phase. Among the changes observed in the weeks preceding the July explosion one of the most significant is represented by the shape variation of the explosions, filtered in the very long period (VLP-2-50 s.) band, recorded by the Sacks-Evertson strainmeter installed near the village of Stromboli. Starting from these observations, we used two independent methods in order to classify events falling in the wider frequency band, including also the ultra long-period (ULP - 50-200 s.) signal. This classification leads us to establish a link between VLP and ULP shape variation forms and volcanic activity, especially related to the unforeseen July, 3 2019 paroxysm. We, therefore, have verified the validity of the obtained results through the use of two different methodologies, the cross-correlation algorithm and an unsupervised machine learning strategy. Furthermore, the results of the conducted research allow the detection of medium-term anomalies leading to vulcanian explosions of Stromboli: several days before the most significant activity, this very sensitive instrument was able to detect VLP and ULP frequency and amplitude variations, linked to the intimate source process of gas-magma injection.